(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the diagnostic accuracy of early arterial phase contrast-enhanced CT imaging in distinguishing hepatocellular carcinoma (HCC) from dysplastic nodules (DN) in cirrhotic patients. Study Design: Cross-sectional observational study conducted at a tertiary care hospital’s radiology department in Lahore. Methods: A total of 73 cirrhotic patients with focal liver lesions detected on screening were recruited using convenience sampling. Multi-phase contrast-enhanced CT scans were performed, with special focus on the early arterial phase ( 30–35 seconds post-contrast injection). Imaging features assessed included lesion size, enhancement pattern, presence of washout, and stromal invasion. Lesions were categorized as HCC or DN based on imaging criteria and clinical/pathologic correlation. Chi-square analysis was used to evaluate associations between imaging features and lesion type, and diagnostic performance (sensitivity, specificity, positive predictive value [PPV], negative predictive value [NPV]) of early arterial phase imaging was calculated against the reference standard diagnosis. Results: The mean age of patients was 29±6 years, with 72.6% male. All patients had chronic liver disease (commonly hepatitis-related or alcohol-related cirrhosis). Early arterial phase CT revealed that both HCC and DN lesions predominantly showed heterogeneous enhancement (>75% of lesions). However, hallmark features distinguishing HCC from DN were identified. Arterial-phase washout was observed in 61.6% of HCCs versus only 17.8% of DNs. Similarly, stromal invasion was evident in 82.2% of HCCs compared to 23.3% of DNs. These differences were statistically significant (p < 0.001). Early arterial phase imaging correctly identified HCC with a sensitivity of 91.6% and specificity of 72.7%, while for DNs the sensitivity was 87.5% and specificity 72.7%. The PPV for HCC was 88% and NPV 80%, indicating high accuracy in confirming HCC and a reasonable ability to rule it out. Conclusion: Early arterial phase CT imaging provides high diagnostic sensitivity for HCC in cirrhotic patients and significantly aids in differentiating HCC from dysplastic nodules. Characteristic arterial-phase findings such as contrast washout and stromal invasion are much more frequent in HCC than in DN, improving confidence in non-invasive diagnosis. Incorporating an early arterial phase in routine liver imaging protocols is recommended to enhance early detection and proper characterization of HCC in at-risk cirrhotic populations.